Self‐rated health and medicine beliefs among older hospital outpatients in Hong Kong. (20th February 2019) - Wan, Bosco; Ball, Patrick; Jackson, David; Maynard, Gregg
Abstract: Objectives: (1) To identify any demographic characteristics, which predict medicines adherence by reporting Necessity‐Concern Differential (NCD) and Self‐Reported Health (SRH) scores among Hong Kong hospital outpatients. (ii) To investigate any association between SRH and NCD in this cultural group. Methods: A total of 709 outpatients completed a questionnaire consisting demographic information, SRH and Belief about Medicines Questionnaire. Findings were analysed statistically. Key findings: Descriptive statistics suggested that older participants (mean age > 64 years) tended to report low SRH, but high NCD compared to younger respondents (mean age < 53 years). Males were more likely to return high SRH and NCD scores than females (56.9 versus 42.2% and 74.8 versus 64.6%, respectively). Chi‐squared tests demonstrated that socio‐economic status was not significantly associated with SRH and NCD reporting ( P  > 0.05). Logistic regressions indicated gender and age groups (young‐old and old‐old) were significant predictors of SRH reporting ( P  < 0.001). Moreover, patients with high SRH were more likely to report high NCD than those with low SRH ( P  = 0.02; OR = 1.53; 95%CI 1.07–2.20). This indicates that regular administration of the SRH item followed by specific questioning could enhance early identification of potential medicine non‐believers and, subsequently, non‐adherent patients who may require urgent interventions or monitoring. Conclusions: Demographic characteristics and significant association between SRH and NCD reporting support our claim that SRH opens new opportunities for prompt identification of potentially non‐adherent patients. However, further interviews to determine the cause(s) of non‐adherence are necessary to validate such findings.